2018
DOI: 10.1186/s40663-018-0145-z
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem management in paludified boreal forests: enhancing wood production, biodiversity, and carbon sequestration at the landscape level

Abstract: Canada's boreal forest represents an important contributor of the world's wood supply industry. However, maintaining or increasing productivity of the boreal forest may be challenging in areas dominated by forested peatlands. Moreover, sustainable management of these forests must also consider other important aspects of the forest ecosystem such as biodiversity and carbon sequestration. To address these concerns, ecosystem-based management has been implemented in some Canadian jurisdictions, such as in regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 93 publications
0
27
0
Order By: Relevance
“…These management practices—favoring organic layer decay—are performed with different considerations for the impact they generate on both atmospheric and aquatic CO 2 and CH 4 fluxes. The most extensive studies have been conducted in Finland 14 , 47 , 48 , while in Canada the C sequestration function of peat soils and carbon accounting are still rarely taken into account in forested peatland management 49 , 50 . Yet, the value of organic horizons for C sequestration highlighted in the present study suggests that the loss of carbon from peat layer disturbance or removal cannot be offset within a short-term period (e.g., 200 years) by enhanced tree growth.…”
Section: Discussionmentioning
confidence: 99%
“…These management practices—favoring organic layer decay—are performed with different considerations for the impact they generate on both atmospheric and aquatic CO 2 and CH 4 fluxes. The most extensive studies have been conducted in Finland 14 , 47 , 48 , while in Canada the C sequestration function of peat soils and carbon accounting are still rarely taken into account in forested peatland management 49 , 50 . Yet, the value of organic horizons for C sequestration highlighted in the present study suggests that the loss of carbon from peat layer disturbance or removal cannot be offset within a short-term period (e.g., 200 years) by enhanced tree growth.…”
Section: Discussionmentioning
confidence: 99%
“…As known, steppe ecological conditions (dry climate and lack of moisture), as well as technogenesis environmental conditions (anthropogenic activities, pollution of air and soil) negatively effect on the trees life. However, the dendrometric parameters of forest park stands (stem density, stem height, stem diameter, stand volume, stand basal area) in Background ecological areas were similar to the natural forest (Lafleur et al, 2018;Kuuluvainen and Gauthier, 2018). This phenomenon can only be explained by the location of some parks.…”
Section: Discussionmentioning
confidence: 87%
“…Such forest management of the highly paludified areas would not require any practices that lead to soil disturbing (i.e., field preparation), and therefore could enhance soil organic carbon storage. Indeed, from a climate change perspective, one of the advantages of the use of management solutions with no or little soil disturbance (i.e., partial and selection cuts) is that they would have a positive effect on the amount of carbon stored in the soil OL (i.e., soil carbon stocks) in paludified forest soil [35]. From management implications perspective, the results of this study are important for landscape management for several reasons: (i) we have demonstrated the potential of LiDAR data to provide spatially detailed topographic information that can be used as sources of data in managing, planning and optimization of forest management activities in paludified boreal forests;…”
Section: Discussionmentioning
confidence: 99%